2019
DOI: 10.1080/15592324.2019.1621246
|View full text |Cite
|
Sign up to set email alerts
|

Repetitive pruning ofSerianthesnursery plants improves transplant quality and post-transplant survival

Abstract: Information on the best methods for producing endangered Serianthes nelsonii plants for use in species recovery projects is lacking. Plants of this species behave similarly in a nursery setting to plants of the congeneric Serianthes grandiflora and Serianthes kanehirae. Container-grown plants of these two species were repeatedly pruned in the nursery to determine if a more favorable root:shoot ratio would result, then to determine if performance after out-planting would benefit from the enhanced root growth. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…The leaves for this study were obtained from nursery plants grown at the University of Guam. Nursery protocols conformed to previously described methods [ 33 , 34 , 35 ]. Seeds were germinated in 10-cm diameter containers in November 2014 under 50% sunlight transmission.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The leaves for this study were obtained from nursery plants grown at the University of Guam. Nursery protocols conformed to previously described methods [ 33 , 34 , 35 ]. Seeds were germinated in 10-cm diameter containers in November 2014 under 50% sunlight transmission.…”
Section: Methodsmentioning
confidence: 99%
“…Earlier observations and experimental treatments indicated Serianthes plants produced with traditional container nursery protocols develop inadequate root growth in relation to shoot growth, and periodic stem tip pruning during nursery production increased relative root growth and mitigated rapid post-transplant mortality [ 35 ]. The excised leaves for this study were derived as a byproduct from pruned stem portions that resulted from stem tip pruning of S. nelsonii stock in August 2015.…”
Section: Methodsmentioning
confidence: 99%
“…Second, S. nelsonii saplings that are grown rapidly under shade in a container nursery do not develop adequate root systems to sustain plant health and viability after transplantation to a field site [32]. Repetitive heading back pruning of the stem leader to temporarily stop stem extension may be one method that improves the relative root growth of containergrown plants [32]. Because destructive techniques are needed to unambiguously quantify root growth, S. kanehirae and Serianthes grandiflora Benth.…”
Section: The Structural Organsmentioning
confidence: 99%
“…To date, not a single tree has been nurtured to maturity and little progress has been made toward reaching these goals. In situ regeneration and horticultural propagation are not limitations to species recovery [18][19][20]. In contrast, in situ recruitment to the sapling stage and successful establishment of nursery stock after out-planting from a nursery are acute limitations.…”
Section: Final Thoughtsmentioning
confidence: 99%
“…A second recent publication discussed how uninformed agents from permitting and funding agencies were critical of the use of pruning as a horticultural tool for Serianthes plant production [19]. Yet the collective evidence to date has revealed that pruning of Serianthes plants exerts no detrimental influence on plant development if the practitioner is a plant physiologist with an understanding of plant water relations [20], and repetitive pruning of plants in a Serianthes nursery greatly improves post-transplant growth and survival [19]. These characteristics of the 25-year Guam case study which dates back to publishing of the S. nelsonii recovery plan [17] illuminate a trait that reduces progress on any formal conservation effort: uninformed agents from federal permitting and funding agencies who are entrusted by the public to plan and execute the conservation agenda.…”
mentioning
confidence: 99%